Study of the possibility of producing semi-hard cheeses from frozen goat’s milk - V. A. Mordvinova; G. M. Sviridenko; I. L. Ostroukhova; D. V. Ostroukhov (Пищевые системы, 2023)
The article presents the results of a study of the quality indicators of semi-hard cheeses produced from defrosted goat’s milk. Natural and defrosted goat’s milk, semi-hard cheeses with a low temperature of the second heating were used as objects of research. Studies of defrosted goat’s milk were carried out after 6±1 days of its storage at a temperature of minus 18°C and subsequent defrosting at a temperature of 37±2°C for 60 minutes; natural goat’s milk — after storage for 24±12 hours at a temperature of 4±2°C. It was found that milk freezing and its subsequent defrosting did not affect the chemical composition of milk and the total content of microorganisms, but the number of somatic cells decreased. Cheeses were produced according to the traditional technological scheme of semi-hard cheese using a bulk mesophilic-thermophilic bacterial starter culture. There was no significant effect of the freezing process of goat’s milk on its technological properties: the duration of curd formation in both variants was (30±1) min, the duration of processing of cheese grain was (90±2) min. The level of syneresis was (55±2)% in the control, (55±6)% — in the test versions and was in the range of error of the method. The degree of transition of dry matter to whey was: in the control — (7.26±0.21)%, in the test — (7.21±0.32)%. It was found that there were no differences in the degree of proteolysis in cheeses during ripening. The values of the acidity the content of available fat in the cheeses of both variants was comparable. The organoleptic characteristics of cheeses at the standard age of 60 days had similar characteristics, both in terms of the degree of intensity of the cheese taste, and in the taste notes of “zest” and “spice”, typical of goat’s milk cheeses. The cheese texture of both variants was characterized as “homogeneous, moderately dense”. It has been established that the process of freezing goat’s milk does not reduce its cheese properties and the qualitative characteristics of the semi-hard cheese produced from it.